2019
DOI: 10.1177/1538574419839255
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Ectopic Variceal Bleed After Pancreas Transplantation With No Portal Hypertension: Case Report and Outcomes of Endovascular Onyx Embolization

Abstract: A 57-year-old male presented with intermittent gastrointestinal bleeding (GIB) 1 year after a successful simultaneous pancreas and kidney transplant. No source could be found after 5 tagged red blood cell studies, 3 computed tomographies (CTs), 7 endoscopies, and 4 catheter angiograms. Review of CTs showed pathologically enlarged superior mesenteric vein branches near a jejunal segment near pancreas graft. Transhepatic superior mesenteric venogram showed varicosities near jejunum, which were obliterated with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Arterial complications after pancreas transplantation can cause massive life-threatening GIB. Ectopic variceal bleeding due to porto-systemic trans-anastomotic varices between the transplant duodenum and recipient small bowel is a rare cause of GIB, with only 2 cases reported in the literature [ 3 , 4 ]. Fontana et al [ 3 ] described peri-transplant duodenal varices in a patient after kidney–pancreas transplant in the setting of portal hypertension, who was treated successfully with coil embolization followed by liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arterial complications after pancreas transplantation can cause massive life-threatening GIB. Ectopic variceal bleeding due to porto-systemic trans-anastomotic varices between the transplant duodenum and recipient small bowel is a rare cause of GIB, with only 2 cases reported in the literature [ 3 , 4 ]. Fontana et al [ 3 ] described peri-transplant duodenal varices in a patient after kidney–pancreas transplant in the setting of portal hypertension, who was treated successfully with coil embolization followed by liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Fontana et al [ 3 ] described peri-transplant duodenal varices in a patient after kidney–pancreas transplant in the setting of portal hypertension, who was treated successfully with coil embolization followed by liver transplantation. Rostambegi et al [ 4 ] reported a similar patient in whom variceal embolization was performed but who subsequently required surgical resection of the involved segment of bowel due to recurrent bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-traumatic and iatrogenic bleeding, especially pseudoaneurysms, may also be successfully embolized with Onyx [6]. Onyx can now be used in a wide range of procedures, including interventions in the venous district (esophageal varices, portal vein embolization), gastrointestinal bleeding embolization (Figure 2) and bronchial artery embolization (Figure 3a,b) [5,6,[9][10][11][12][13][14][15].…”
Section: Gluementioning
confidence: 99%
“…Cyanoacrylate is a highly adaptable adhesive and can be used in a wide variety of endovascular procedures: peripheral and gastrointestinal embolization (even in the presence of coagulopathies; Figure 5), arteriovenous vascular malformations (Figure 6), type-II endoleak embolization of aortic aneurysms, treatment of venous district conditions (esophageal varices, portal vein embolization), oncological treatment (both palliative and preoperative), and bronchial artery embolization for the treatment of hemoptysis [12,15,18,20,21,[25][26][27][28][29].…”
Section: The Continuous Column Techniquementioning
confidence: 99%